Die deutschsprachige Forschung zur Transformation politischer Systeme in Asien: Perspektiven, Profile und Befunde - Croissant, Aurel (Asien, 2017)
German scholars have long neglected the analysis of political transformation pro-cesses in South, Southeast, and Northeast Asia. Only since the end of the 1990s have researchers in Germany developed an interest in this international, mostly English-language, literature. In contrast, German-language political science democ-ratization research on Asia has long been well established. As in North America, the boundaries between democratization and autocracy research have become blurred in recent years — while the close link between democracy and dictatorship research is a welcome development. Theoretically and methodologically, the German-language transformation research on Asia has made only a comparatively small contribution to international political science research. Its main advance has been in its in-depth analysis of individual or select cases. In order to remain internationally pertinent and to become more widely accepted, German-language research hence-forth needs to be more methodologically nuanced as well as to embrace the triangulation of data and mixed-methods research designs. (Asien/GIGA)